Disrupting the Disruption: A Digital Learning HeXie Ecology Model - Na Li; Henk Huijser; Youmin Xi; Maria Limniou; Xiaojun Zhang; Megan Yih Chyn A. Kek (MDPI AG, 2022)
Broad societal disruptions (i.e., the industrial revolution, digitalisation, and globalisation) have created a need for an increasingly adaptive higher education system in recent decades. However, the response to these disruptions by universities has generally been slow. Most recently, online learning environments have had to be leveraged by universities to overcome the difficulties in teaching and learning due to COVID-19 restrictions. Thus, universities have had to explore and adopt all potential digital learning opportunities that are able to keep students and teachers engaged in a short period. This paper proposes a digital learning HeXie ecology model, which conceptualises elements and relationships pertaining to the societal need for a more agile and digitally resilient higher education system that is better placed to confront disruptive events (such as pandemics) and that is able to produce graduates who are well-equipped to deal with disruption and uncertainty more broadly. Specifically, we propose a digital learning ecology that emphasises the role of self-directed learning and its dynamic interaction between formal, informal, and lifelong learning across a five-level ecosystem: the microsystem, mesosystem, exosystem, macrosystem, and chronosystem. This study contributes to the theoretical literature related to flexible learning ecologies by adopting and incorporating the Chinese HeXie concept into such ecologies.